1998
DOI: 10.1038/sj.bmt.1701435
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing haemopoietic recovery following chemotherapy-mobilised autologous peripheral blood progenitor cell transplantation for haematological malignancies: a retrospective analysis of a 10-year single institution experience

Abstract: Summary:We retrospectively analysed the factors that influenced rate of haemopoietic recovery (HR) in 243 patients after transplantation with chemotherapy-mobilised autologous peripheral blood progenitor cells (PBPC). Approximately half the patients also received haemopoietic growth factors (HGF) for mobilisation. Conditioning for transplantation was with either chemotherapy alone or chemotherapy plus total body irradiation (TBI). Median time to recovery of granulocytes у0.5 ؋ 10 9 /l was 13 days (range 7-93 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…4 In this report, however, important variables such as the amount of previous chemotherapy or the dose of CFU-GM or CD34 + cells infused were not analyzed. Finally, in a recent study by Lowenthal et al, 5 platelet recovery was slower in patients with acute leukemia than in other diseases. In the multivariate analysis, the conditioning regimen, but not the diagnosis, remained as a significant independent factor influencing HR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In this report, however, important variables such as the amount of previous chemotherapy or the dose of CFU-GM or CD34 + cells infused were not analyzed. Finally, in a recent study by Lowenthal et al, 5 platelet recovery was slower in patients with acute leukemia than in other diseases. In the multivariate analysis, the conditioning regimen, but not the diagnosis, remained as a significant independent factor influencing HR.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In a series of 145 patients, including 31 patients with acute leukemia, Haas et al 3 showed that the leukemia group had delayed HR when compared with other diagnoses. However, in that study, there was a remarkable difference between the patient groups with regard to the amount of CFU-GM Bone Marrow Transplantation infused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[44][45][46][47][48][49][50][51][52][53] The current results underline that further investigation of this topic Figure 4. Calibration of the model to different clinical scenarios: (a) autologous PBSC with and without post transplant cytokine administration; patient data taken from Lowenthal et al 27 (b) Allogeneic HLA-identical PBSC without post transplant cytokine administration; patient data taken from trials by Vigorito et al 30 and Bensinger et al 31 (c) Allogeneic HLA-identical PBSC with post transplant cytokine administration; patient data taken from different trials. [28][29] (d) Allogeneic HLA-haplo-identical PBSC with and without post transplant cytokine administration; patient data taken from trials by Aversa et al 32 and Kato et al 33 Model has been scaled to the fraction of patients alive and engrafted after 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…As various diseases are treated by PBSC transplantations (PBSCT), we focus on trial data including different diagnoses. We consider the following scenarios used in current clinical practice: autologous PBSCT with and without post transplant cytokine administration, 19,27 HLA-identical allogeneic PBSCT with 28,29 and without 30,31 post transplant cytokine administration, haplo-identical PBSCT 32,33 and umbilical cord blood transplantation. 34 We also consider the impact of reduced conditioning regimens.…”
Section: Methodsmentioning
confidence: 99%